Student Study Guide to Accompany Adolescent Development - Dacey J.; Kenny M.; Vestal L. B. (Madison Dubuque Brown & Benchmark Publishers, 1994)
This book looks at both early and late adolescence, including current research emphasizing the distinctiveness of these two periods. "Applied view boxes" are found throughout the text, providing ideas for students who will be teaching, counselling or parenting adolescents. Chapters on stress, substance abuse, and delinquent behaviour provide comprehensive coverage of adolescent problems and disturbances. A comprehensive learning aid system includes: a built-in list of learning objectives, "What's Your View?" boxes, "What Do You Think?" questions in every chapter, as well as frequent direct address in the text to help students get involved in the subject matter.
Keywords: 159.9